SIKLUS HIDUP BULU BABI (Echinometra mathaei) LIFE CYCLE OF SEA URCHINS (Echinometra mathaei) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT: Life cycle of sea urchin was examined by cultivation in the laboratory. The cultivation has been successful to a scale where it can play a role both in population enhancement and food production. Sea urchin can be raised in the laboratory with proper condition. Larval development of the urchins consists of 2-arm , 4-arm, 6-arm, and 8-arm, respectively. The larvae can be grown to metamorphosis stage in about three weeks. Sexual maturity can be reached in about a year after metamorphosis. By then the urchin is about 21,58-0,16 mm in length of diameter. This research is a first step and an outline of the techniques for raising sea urchin. It serves as a basis for further studies on mass production of sea urchins.